Description of the EUROBIS Program: A Combination of an Epode Community-Based and a Clinical Care Intervention to Improve the Lifestyles of Children and Adolescents with Overweight or Obesity - Mazzeschi, Claudia (Hindawi Publishing Corporation, 2014)
The present paper describes the Epode Umbria Region Obesity Prevention Study (EUROBIS) and aims to implement the C.U.R.I.A.MO. model through the EPODE methodology. The main goal of the EUROBIS is to change the pendency of slope of the actual trend towards the increase in the yearly rates of childhood overweight and obesity in Umbria and to improve healthy lifestyles of children and their parents. The project is the first EPODE program to be performed in Italy. The aims of the Italian EUROBIS study are: (1) a community-based intervention program (CBP) carrying out activities in all primary schools of the Umbria Region and family settings as first step, to reverse the current obesity trend on a long-term basis, and (2) a clinical care program for childhood and adolescent by C.U.R.I.A.MO. model. C.U.R.I.A.MO. model is a multidisciplinary approach to improve three key aspects of healthy lifestyles: nutrition, exercise, and psychological aspects with the strategy of a family-based approach. The community-based intervention and clinical trial provide an innovative valuable model to address the childhood obesity prevention and treatment in Italy.